Role of the community pharmacist in emergency contraception counseling and delivery in the United States: current trends and future prospects - Rafie S; Stone RH; Wilkinson TA; Borgelt LM; El-Ibiary SY; Ragland D (Dove Medical Press, 2017)
Sally Rafie,1 Rebecca H Stone,2 Tracey A Wilkinson,3 Laura M Borgelt,4,5 Shareen Y El-Ibiary,6 Denise Ragland7 1Department of Pharmacy, UC San Diego Health, San Diego, CA, 2Department of Clinical and Administrative Pharmacy, University of Georgia, College of Pharmacy, Athens, GA, 3Children’s Health Services Research, Department of Pediatrics, Indiana University School of Medicine, Indianapolis, IN, 4Department of Clinical Pharmacy, 5Department of Family Medicine, Skaggs School of Pharmacy and Pharmaceutical Sciences, University of Colorado, Aurora, CO, 6Department of Pharmacy Practice, College of Pharmacy, Midwestern University, Glendale, AZ, 7Department of Pharmacy Practice, College of Pharmacy, University of Arkansas for Medical Sciences, Little Rock, AR, USA Abstract: Women and couples continue to experience unintended pregnancies at high rates. In the US, 45% of all pregnancies are either mistimed or unwanted. Mishaps with contraceptives, such as condom breakage, missed pills, incorrect timing of patch or vaginal ring application, contraceptive nonuse, forced intercourse, and other circumstances, place women at risk of unintended pregnancy. There is a critical role for emergency contraception (EC) in preventing those pregnancies. There are currently three methods of EC available in the US. Levonorgestrel EC pills have been available with a prescription for over 15 years and over-the-counter since 2013. In 2010, ulipristal acetate EC pills became available with a prescription. Finally, the copper intrauterine device remains the most effective form of EC. Use of EC is increasing over time, due to wider availability and accessibility of EC methods. One strategy to expand access for both prescription and nonprescription EC products is to include pharmacies as a point of access and allow pharmacist prescribing. In eight states, pharmacists are able to prescribe and provide EC directly to women: levonorgestrel EC in eight states and ulipristal acetate in seven states. In addition to access with a prescription written by a pharmacist or other health care provider, levonorgestrel EC is available over-the-counter in pharmacies and grocery stores. Pharmacists play a critical role in access to EC in community pharmacies by ensuring product availability in the inventory, up-to-date knowledge, and comprehensive patient counseling. Looking to the future, there are opportunities to expand access to EC in pharmacies further by implementing legislation expanding the pharmacist scope of practice, ensuring third-party reimbursement for clinical services delivered by pharmacists, and including EC in pharmacy education and training. Keywords: pharmacist, community pharmacy, emergency contraception, levonorgestrel, ulipristal acetate, intrauterine device